Hubungan Perilaku Mencuci Tangan Dengan Kejadian Diare Pada Anak Di Wilayah Kerja Puskesmas Cirimekar Tahun 2023 - Khairani Niska; Nurul Ainul Shifa; Risky Kusuma Hartono (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
Diarrhea is a condition where there is increased defecation due to an infection. Children can be said to have diarrhea if the volume of stool is measured at 10ml/kg per day. According to the World Health Organization (WHO) 2020, the benefit of washing hands is to keep hands clean, not only as an effective defense against the spread of infections and serious diseases. The aim of the research was to determine the relationship between hand washing and the incidence of diarrhea in children in Cibinong District. This type of research is quantitative research. The research design used is correlational research with a controlling approach. The sampling technique uses total sampling. The number of samples in this research is 30 medical records of children suffering from diarrhea at the Cirimekar Community Health Center. In this research, the Chi-Square statistical test is used. . The results show that the relationship between hand washing behavior and the incidence of diarrhea shows that the P-Value is 0.001 <0.05, so it can be concluded that there is a significant relationship between hand washing behavior and the incidence of diarrhea in children in the Cirimekar Health Center Working Area. The conclusion of this research is that there is a relationship between hand washing behavior and the incidence of diarrhea in children in the Cirimekar Health Center Working Area in 2023.